(untitled) (Computer systems and information technologies, 2022)
Wireless Data Media (WDM) provide data exchange between subscribers who can perform a single tasks in the conditions of active electronic influence. That is why it is important an indicator that characterizes the effectiveness of such WDM is the ability to ensure a given reliability of information reception in the conditions exposure to interference of various origins, including intentional, which characterized by high power spectral density. Effective the direction of counteraction to disturbances is application in WDM of technologies of expansion signal spectrum and code constructions. The purpose of the research is to increase effectiveness of WDM in the conditions of influence of disturbances through ensuring reliability information through the development of methods based on adaptive coding and their using. To develop technology to ensure the reliability of information in WDM on the basis of adaptation of code constructions methods of the theory of management were used, coding, decision making, adaptive systems, optimization, communication, simulation, noise-tolerant coding theory, information theory. The results of the research permit: to ensure reliability of information of departmental radio communication systems under impact of intentional jamming; to quantify reliability of information of departmental radio communication systems under impact of intentional jamming; to choose control parameters in selecting an operating mode of radio communication equipment; on the basis of the developed results to design components of modem equipment for means of departmental radio communication. The results of the study should be used by industrial and research organizations in order to ensure the reliability of adaptive programmed radio stations in conditions of intentional interference.